Cycloartane and Stigmastane Type Triterpenoids from Pothos scandens Inhibit Estradiol (E2) Induced Proliferations in Breast Cancer Cells (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Four cycloartane type triterpenoids and three stigmastane type steroids were isolated from the methanolic extract of stem and root part of Pothos scandens L. (Araceae), a Bangladeshi medicinal plant by high performance liquid chromatographic technique. The compounds were characterized as 24-methylenecycloartanol (1), 24-methylenecycloartenone (2), 24-en-cycloartenone (3), 24-methylenecycloartanyl ferulate (4), stigmast-4-en-3-one (5), stigmast-4,22-diene-3-one (6) and β-sitosterol glucoside (7) through extensive 1D and 2D NMR spectroscopic studies. All the isolates were evaluated for their estrogenic/antiestrogenic activity using the estrogen-responsive breast cancer cell lines, MCF-7 and T47D. The results showed that all the compounds possess mild to strong antiestrogenic activity in both cell lines which was compared to positive control tamoxifen. 24- Methylenecycloartanol (1), which contains a hydroxyl group in its C-3 position, inhibited 90% of estradiol (E2)- induced cell proliferation in MCF-7 and T47D cell lines at a concentration of 0.01 μM only. 24- Methylenecycloartanyl ferulate (4) and stigmast-4,22-diene-3-one (6) showed 90% of estradiol (E2)-induced cell proliferation in T47D cell only at a concentration of 0.01 μM whereas 10.0 μM was required for 24- methylenecycloartanyl ferulate (4) for the same activity in MCF-7 cells. This is the first report of isolation of these compounds from the plant along with their antiestrogenic property.Dhaka Univ. J. Pharm. Sci. 18(1): 93-102, 2019 (June)